Inclusive education and the challenges of publishing in indigenous languages in Nigeria (2013)
Inclusive education is a desired approach for strengthening the capacity of education. It addresses the needs of all learners and facilitates access to teaching and learning materials out of which book is principal. Books are basic to schooling which makes publishing vital to education. The National Policy on Education (2004) makes provision for employing indigenous languages for teaching at the primary level of education which is a boost to inclusive education. It is however disheartening that many indigenous languages are endangered. Due to the 'unpopular' nature of the languages and the decreasing number of users by the day, writing and publishing in indigenous languages is faced with stiff ling challenges. Preliminary investigations show that generally, there is dearth of indigenous languages publishers, and logically, there are fewer for inclusive education. The few who do, grapple with series of challenges. It is this resultant challenges to publishing for inclusive education that this paper discusses. Structured into six parts, the study examines the concepts of inclusive education and indigenous languages, the Nigeria publishing system and the persons with special needs, the Nigerian languages and the challenges of publishing for persons with special needs, technical and production challenges, and remedies for the challenges. It is recommended that a spirited effort on the part of the government will bring in a turnaround and be a boost for inclusive education.